Urgensi Shalawat bagi Mentalitas Mahasiswa Jurusan Tasawuf Psikoterapi - Febi Marsha Putri (Gunung Djati Conference Series, 2023)
This study aims to discuss the urgency of prayer for the mentality of students majoring in psychotherapy. This study uses a qualitative approach by applying a descriptive-analytical method. The results and discussion in this study indicate that the specialty of someone who is accustomed to reciting blessings is that in his heart the personality that the Prophet taught will be created. So the extraordinary personality of a person who practices blessings in his life is because automatically the personality of the Prophet, the most perfect human being on earth, will be reflected in him. So do not be surprised if someone who practices prayer has good behavior, habits and perspective. Their mentality is stronger than students who don't practice blessings. This study concludes that students who practice prayer have a strong mentality such as the ability to control emotions well so that all obstacles, challenges and obstacles that are usually encountered by a student in general will be easy for them to face and solve well. As well as by practicing this prayer, it is a bridge to lead students majoring in psychotherapy tasawuf to happiness and success in the afterlife.